Atlantic water flow into the Arctic Ocean through the St. Anna Trough in the northern Kara Sea. Issue 7 (23rd July 2015) - Dmitrenko, Igor A.; Rudels, Bert; Kirillov, Sergey A.; Aksenov, Yevgeny O.; Lien, Vidar S.; Ivanov, Vladimir V.; Schauer, Ursula; Polyakov, Igor V.; Coward, Andrew; Barber, David G.
Abstract The Atlantic Water flow from the Barents and Kara seas to the Arctic Ocean through the St. Anna Trough (SAT) is conditioned by interaction between Fram Strait branch water circulating in the SAT and Barents Sea branch water—both of Atlantic origin. Here we present data from an oceanographic mooring deployed on the eastern flank of the SAT from September 2009 to September 2010 as well as CTD (conductivity‐temperature‐depth) sections across the SAT. A distinct vertical density front over the SAT eastern slope deeper than ∼50 m is attributed to the outflow of Barents Sea branch water to the Arctic Ocean. In turn, the Barents Sea branch water flow to the Arctic Ocean is conditioned by two water masses defined by relative low and high fractions of the Atlantic Water. They are also traceable in the Nansen Basin downstream of the SAT entrance. A persistent northward current was recorded in the subsurface layer along the SAT eastern slope with a mean velocity of 18 cm s−1 at 134–218 m and 23 cm s−1 at 376–468 m. Observations and modeling suggest that the SAT flow has a significant density‐driven component. It is therefore expected to respond to changes in the cross‐trough density gradient conditioned by interaction between the Fram Strait and Barents Sea branches. Further modeling efforts are necessary to investigate hydrodynamic instability and eddy generation caused by the interaction between the SAT flow and the Arctic Ocean Fram Strait branch water boundary current.